Perceived positive humorous leadership and university students’ creativity: The mediating role of creative self-efficacy - Chen, Ling-Ge; Huang, Jian-Hao (Edelweiss Applied Science and Technology, 2025)
This study investigates the mediating role of creative self-efficacy in the relationship between perceived positive humorous leadership and creativity among university students. A total of 591 undergraduate students from two universities in China participated in the research. Data were collected using validated instruments, including the Positive Humorous Leadership Scale, the Creative Self-Efficacy Scale, and the Creativity Scale. Descriptive statistics and correlation analyses indicated significant and positive associations among perceived positive humorous leadership, creative self-efficacy, and creativity. Mediation analysis using structural equation modeling further revealed that creative self-efficacy partially mediated the relationship between perceived positive humorous leadership and creativity. Specifically, students who perceived their instructors as using positive humor were more likely to exhibit higher levels of creative self-efficacy, which in turn was linked to greater creative performance. These findings underscore the importance of instructors’ use of positive humor as a supportive interpersonal resource that fosters students’ confidence in their creative potential and enhances their overall creative output. The study offers valuable theoretical contributions to leadership and creativity research in educational contexts and provides practical implications for promoting creativity through humor-based leadership strategies in higher education settings.